Development of a novel fermented soymilk product with potential probiotic properties - Rossi, Elizeu Antonio [UNESP]; Vendramini, Regina Célia [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Pei, Yang C. [UNESP]; Valdez, Graciela F. de (Springer Nature, 1999)
The study was carried out to test the ability of Enterococcus faecium, Lactobacillus acidophilus, L. jugurti, Streptococcus thermophilus and L. delbrueckii ssp bulgaricus to decrease cholesterol in vitro and to grow in the presence of bile salts. Both properties were dependent on the species under study. The cultures were also inoculated into soymilk fortified with dry milk whey powder as single or mixed starters. The physicochemical and sensory evaluations of the fermented products showed that E. faecium plus L. jugurti (ratio 1:1) is the best combination, and this mixture also produces a 43% decrease in cholesterol. © Springer-Verlag 1999.
Keywords: Enterococcus faecium; Lactic acid bacteria; Probiotic; Soymilk products